Satire Horatian-Based Literature Learning in Higher Education - M. Firdaus; Syahrul, R, Agustina; Harris Effendi Thahar (Researchparks Publishing, 2021)
Poetry, as a kind of literature, is one of the right mediums to describe inequalities, social conditions and at the same time criticize social conditions. As intellectuals, students have a duty of conscience to always be responsible for the social, economic and political situation of the nation. Criticism should be conveyed in language that remains polite and courteous so as not to insult or incite hate. The satirical style of language is effective as a tool for critique through literary texts. This study includes library research. The results show that: 1) a sense of humor from Horatian satire can increase students' motivation in learning; 2) Horatian satire must have sharp thinking and linguistic intelligence; 3) Using Horatian satire can prevent hate speech; 4) Learning to write satire-based literature can improve students' critical, active and productive thinking skills and students' politeness of language. Through poetry, which has a unique and aesthetic language, and with a satire-horatian style, criticism can certainly be done well and accompanied by sharpness of thought.